Akurasi Jadwal Salat Digital Menggunakan Aplikasi Khalifah JWS ESP di Kecamatan Banda Sakti Kota Lhokseumawe - Muhammad Diva Saputra; Hasna Tuddar Putri (Islamic Astronomy Department, Sharia and Law Faculty, 2023)
Determination of prayer times is practically a primary requirement in Islam. The mosque's digital prayer schedule is now an alternative reference in starting prayer times. The reason is that in Papkandang it is enough to provide a very easy solution in starting and ending prayers. Many mosques among the community use digital prayer schedules. There are three mosques in the Banda Sakti sub-district, Lhokseumawe City that use digital prayer schedules based on the same application, namely the Khalifah JWS ESP, namely the Darussalam mosque, Syuhada, Islamic Center. This study discusses the Accuracy of Digital Prayer Schedules Using the JWS ESP Khalifah Application in Banda Sakti District, Lhokseumawe City. The formulation of the research problem is how to work and the accuracy of digital prayer schedules using the Khalifah JWS ESP application. This study uses a qualitative approach and applies arithmetic (science of reckoning). Primary data sources are data from digital calculations and prayer schedules at the Darussalam mosque and Syuhada mosque and secondary data sources are references from previous research. Data collection techniques namely observation, interviews, and documentation. Data analysis used a descriptive method. The results showed that the workings of digital clocks at both mosques were application-based and also related to the internet and Wifi and it was better to check once a month by the authorities regarding the prayer schedule. The way it works follows the standard prayer schedule calculation algorithm. As for the level of accuracy, both are said to be accurate, having an average difference of 1 minute. However, there is a difference in how to determine the altitude value where the author takes the value from the height value that has been multiplied and divided by the sun's height value, as for this digital prayer schedule only takes the height value of the place, without any recalculation.